Inorganic perovskite solar cell and preparation method thereof - ZHUANG XUEHENG; ZHANG YING; ZHU YUEJIN; ZENG ZHAOBING; ZHANG JING; CHEN RENJIE (2018)
The invention relates to an inorganic perovskite solar cell and a preparation method thereof. The inorganic perovskite solar cell is characterized by comprising a conductive glass layer, a compact titanium dioxide membrane, a CsPbI2Br crystal membrane, a hole transmission layer and a silver electrode layer which are in a layered shape and are sequentially arranged, wherein lead acetate is doped tothe CsPbI2Br crystal membrane, the CsPbI2Br crystal membrane is prepared from a perovskite solution, the solute of the perovskite solution is CsI, PbI2, PbBr2 and the lead acetate, the solvent of theperovskite solution is DMF and DMSO, and the content of the lead acetate in the perovskite solution accounts for 5-15wt%. The lead acetate is doped to CsPbI2Br, the crystallization of the perovskitemembrane is greatly optimized, the internal charge recombination of the perovskite layer is prevented, so that the open-circuit voltage of the cell is increased, and the efficiency is further improved. 本发明涉及种无机钙钛矿太阳能电池及其制备方法，其特